Graphitic carbon nitride tetragonal hollow prism with enhanced photocatalytic hydrogen evolution. (5th November 2019) - Li, Huiliang; Bao, Xiaolei; Wang, Zeyan; Zheng, Zhaoke; Wang, Peng; Liu, Yuanyuan; Zhang, Xiaoyang; Qin, Xiaoyan; Dai, Ying; Li, Yingjie; Zou, Huiling; Huang, Baibiao
Abstract: Graphitic carbon nitride tetragonal hollow prism (GCN-THP) with nitrogen vacancies was prepared by a simple two-step calcination method. Based on the characterizations of the as-prepared GCN-THP and the intermediate precursor, a possible mechanism was proposed for the formation of GCN-THP. The as-prepared GCN-THP exhibits superior activity and excellent stability during photocatalytic hydrogen evolution under visible light irradiation. The photocatalytic hydrogen evolution rate of GCN-THP was measured to be 1990 μmol g −1  h −1, which is 6.2 times as that of GCN. The enhanced photocatalytic activity could be attributed to unique 1D tetragonal hollow prism morphology and the presence of nitrogen vacancies in the as-prepared GCN-THP, which could increase the surface area, expand the visible light absorption, and promote the charge separation during photocatalytic hydrogen evolution. Our work could provide a new route to synthesize highly efficient photocatalysts with 1D hollow structures. Graphical abstract: Image 1 Highlights: g-C3 N4 tetragonal hollow prism was prepared by a two-step calcination method. Low polymerized melamine serves as the template. The g-C3 N4 hollow prism exhibits a superior HER rate of 1990 μmol g −1  h −1 .